High-frequency profile in adolescents and its relationship with the use of personal stereo devices - Renata Almeida Araújo Silvestre; Ângela Ribas; Rogério Hammerschmidt; Adriana Bender Moreira de Lacerda (Elsevier, 2016)
Abstract Objective: To analyze and correlate the audiometric findings of high frequencies (9-16 kHz) in adolescents with their hearing habits and attitudes, in order to prevent noise-induced hearing loss. Method: This was a descriptive cross-sectional study, which included 125 adolescents in a sample of normal-hearing students, at a state school. The subjects performed high-frequency audiometry testing and answered a self-administered questionnaire addressing information on sound habits concerning the use of personal stereo devices. The sample was divided according to the exposure characteristics (time, duration, intensity, etc.) and the results were compared with the observed thresholds, through the difference in proportions test, chi-squared, Student's t-test, and ANOVA, all at a significance level of 0.05. Results: Average high-frequency thresholds were registered below 15 dB HL and no significant correlation was found between high frequency audiometric findings and the degree of exposure. Conclusion: The prevalence of harmful sound habits due to the use of personal stereo devices is high in the adolescent population, but there was no correlation between exposure to high sound pressure levels through personal stereos and the high-frequency thresholds in this population.